PENINGKATAN KEMANDIRIAN DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL OPEN ENDED LEARNING DENGAN MEDIA MUATAN DI KELAS IV SDN 3 TAMANWINANGUN - Azizah, Nur (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract:The Application of Open Ended Learning Model Using Load Media in Improving Students? Learning Aotonomy and Learning Outcomes of Mathematics Learning about Integersfor the Fourth Grade Students of SD Negeri 3 Tamanwinangun.The objectives of this research is to improve students? learning autonomy and learning outcomes of Mathematics learning for the fourth grade students of SDN 3 Tamanwinangun through the application of Open Ended Learning model using load media. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of five meetings including planning, action, observation, and reflection. Subjects of the research were 33 students of the fourth grade of SD Negeri 3 Tamanwinangun. The results of this research showed that the application of Open Ended Learning using load media can improve students? learning autonomy and learning outcomes of Mathematics learning about integers for the fourth grade students of SD Negeri 3 Tamanwinangun. Keywords: Open Ended Learning, load media, autonomy, Mathematics Abstrak: Peningkatan Kemandirian dan Hasil Belajar Matematika Melalui Model Open Ended Learning dengan Media Muatan di Kelas IV SDN 3 Tamanwinangun. Penelitian ini bertujuan untuk meningkatkan kemandirian dan hasil belajar Matematika siswa kelas IV SDN 3 Tamanwinangun melalui model Open Ended Learning dengan media muatan. Penelitian ini adalah penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus dengan tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas IV SDN 3 Tamanwinangun berjumlah 33 siswa. Hasil penelitian menunjukkan bahwa penerapan model Open Ended Learning dengan media muatan dapat meningkatkan kemandirian dan hasil belajar Matematika tentang bilangan bulat di kelas IV SDN 3 Tamanwinangun. Kata Kunci: Open Ended Learning, media muatan, kemandirian, matematika